The impact of trade tensions on Switzerland: A quantitative assessment - Laurence Wicht (Aussenwirtschaft, 2019)
This paper quantifies the impact of trade tensions between the United States and China. Using a general equilibrium Ricardian trade model, it provides a Swiss-centric analysis of two tariff escalation shocks. Counterfactual analysis shows that welfare and trade effects are broadly negative for the United States and China. In contrast, both tariff escalation shocks could lead to a small increase in real GDP in Switzerland. The labor productivity of Swiss manufacturing sectors increases slightly, especially in sectors that are well-connected to China. While trade collapses between the United States and China, Swiss real exports to the United States in selected sectors increase significantly.
Keywords: F10; F11; F14; 330; gains from trade; tariffs; trade wars